PENGARUH MINAT MEMBACA TERHADAP HASIL BELAJAR MAHASISWA PPKn FKIP UNIVERSITAS RIAU - Lia Charolina Faizah; Sri Erlinda; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This study is based on the lack of interest of students to read textbooks related to PPKn and still many students who rarely use books as the main reference in seeking information. They tend to be more concerned with electronic media such as (Handpone, radio, television, newspapers, etc.)as a reading source rather than reading a book. The lack of interest in reading students is based on the many types of entertainment, games (geme) and television shows that can distract students to read books. The formulation of the problem in this research is: how the influence of reading interest on student learning outcomes PPKn FKIP University of Riau. This research was conducted in PPKn FKIP Universias Riau Pekanbaru in March-May 2017. The sample of this research is as many as 44 students with Proportional Random Samling technique. Technique of collecting data through observation, interview, questionnaire, documentation. And analysis technique use quantitative descriptive analysis by using Simple Linear Regression equation with process through SPSS Application version 17.00. To prove the hypothesis then tested the validity by comparing the value of r arithmetic with r table at the level of significance of 5% for 2-sided test. If r arithmetic> r table then the measuring instrument used is valid and vice versa, if r arithmetic ≤ r table then the measuring tool used is not valid. R value of table can be obtained with equation N - 2 = 44 - 2 = 42 = 0,297 to see the influence of each indicator. Based on the significance test conducted in this study showed a significant influence significant reading interest (X) on the learning outcomes of students PPKn (Y) is characterized by thitung = 5.808 > ttable = 2.018 with sig. (0.000) < (0,05) thus Ho is rejected and Ha accepted. This means reading interest has a significant effect on student learning outcomes PPKn FKIP University of Riau.Key Words: Reading Interest, Learning Outcomes